Utilizing Online Dictionary Game to Empower Students’ Vocabulary Acquisition at Junior Secondary School: A Case Study at SMP Negeri 12 Tamalanrea Makassar - Abidin Pammu (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Abstract Vocabulary acquisition has been the main concern of the researchers around the globe but still little can be reported about what best strategies to enhance vocabulary learning. The main concern of the present study is improvement of vocabulary learning by means of online dictionary game one of the leading secondary schools in Makassar. The main objective is to help teacher empower their teaching aids in order to strengthen the ability of learners in improving their own lexical items beyond school instruction. A mixed-method research design was utilized in undertaking the research. Thirty (30) students were randomly selected out of a 120 total population of the second grade as the sample of the study. The quantitative method was obtained from pre-test and post-test result. Meanwhile, the qualitative method was obtained from the results of in-depth interview analysis. The results confirm that almost all students make a significant increase on the achievement of vocabulary acquisition after the intervention. This study confirms very strong assurance that online vocabulary learning utilizing dictionary provides a substantial basis for EFL successful teaching and learning in Indonesian context.The research bears significant pedagogical implications for Indonesian teachers to constantly push their students to use dictionary, notably online dictionary that they can easily access through their mobile phone. Keywords: Vocabulary, Improve, Game, Online, Acquisition